Competency Suitability to Increase the Effectiveness of Riau Islands Vocational High School Graduates - Abdul Mukti; Mukhtar Latif; Kasful Anwar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study uses a qualitative approach that describes the object studied through the process of exploring facts and data on objects in the field as they are, to achieve these objectives, data is needed that is excavated from an in-depth observation process with the principal, vice principal, head of the welding and metal fabrication engineering expertise program and teachers of productive subjects. Data collection techniques using in-depth interviews with, participant observation, and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions or verification. Checking the validity of the data using triangulation methods. The results of the study indicate that the suitability of students' technical and non-technical competencies with industry needs greatly determines the success rate of graduates in the workforce. Relevant competencies, such as mastery of modern welding technology and soft skills such as communication and teamwork, are key factors. In addition, it was found that aligning the curriculum with industry standards and the active involvement of industry partners through internship programs contributed significantly to improving the quality of graduates. This study recommends strengthening cooperation between vocational schools and the industrial world and developing training programs based on labor market needs.